Implementasi Manajemen Pendidikan Karakter dalam Pembinaan Akhlak Peserta Didik - Taufiqur Rahman; Siti Masyarafatul Manna Wassalwa (Jurnal Pendidikan Islam Indonesia, 2019)
Planning of character education management for students by involving stakeholders, committees, village heads, religious leaders and the local community is contained in the school rules. The implementation of character education management involves all elements of the school to create a useful development for students’ character. The assessment of character education management is in the form of observation for all teachers associated in the process of assessing students’ character by reporting students’ progress. This guidance is through preventive, curative and repressive measures. The assessment of character education management takes the form of observation of all teachers involved in the process of assessing the character of students by taking notes on the development of students.